2019
DOI: 10.1111/modl.12594
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Advanced Heritage Language Learners’ Peer Interaction Across Modes and Pair Types

Abstract: A strand of task‐based interaction research has emerged to better understand the effects of heritage language (HL) and second language (L2) learners’ peer collaboration on interactional moves (e.g., language‐related episodes [LREs], self‐repairs) and linguistic focus. To extend this line of research, this study compared 14 HL–L2 and 16 HL–HL advanced learners’ peer interactions across face‐to‐face (FTF) and written synchronous computer‐mediated communication (SCMC) modes. Each dyad completed 2 decision‐making/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 49 publications
(97 reference statements)
2
23
2
Order By: Relevance
“…Unlike the TxtSCMC condition in which peers wrote out their sentences and phrases in the Skype chat window, the mismatch between the written task and the AudSCMC and VidSCMC modes required those dyads to engage more in addressing mechanics because they needed to put into written form their ideas produced during spoken communication. This finding contrasts with Torres and Cung (2019) who found no significant differences with regards to spelling and accent placement between the TxtSCMC and face-to-face conditions using the same decision-making/writing task in Spanish. Torres and Cung (2019) and the current study differed in the proficiency level of the participants.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Unlike the TxtSCMC condition in which peers wrote out their sentences and phrases in the Skype chat window, the mismatch between the written task and the AudSCMC and VidSCMC modes required those dyads to engage more in addressing mechanics because they needed to put into written form their ideas produced during spoken communication. This finding contrasts with Torres and Cung (2019) who found no significant differences with regards to spelling and accent placement between the TxtSCMC and face-to-face conditions using the same decision-making/writing task in Spanish. Torres and Cung (2019) and the current study differed in the proficiency level of the participants.…”
Section: Discussioncontrasting
confidence: 99%
“…We first found that the AudSCMC and VidSCMC groups significantly produced more LREs than the TxtSCMC group. This result replicates previous findings in which fewer LREs were generated in TxtSCMC in comparison with face-to-face conditions with groups of intermediate-level English and advanced-level Spanish learners (Hamano-Bunce, 2011;Rouhshad & Storch, 2016;Torres & Cung, 2019). Further, in line with Yanguas and Bergin (2018), no significant differences emerged between the VidSCMC and AudSCMC groups.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations